A prospective randomised control trial to study the role of intra-peritoneal instillation of ropivacaine versus normal saline irrigation in reduction of post-operative pain in patients undergoing laparoscopic cholecystectomy. - Pankaj, S; Pankaj, D; Sushil, M; Harnam, S (Department of Surgery, UKM Medical Centre, 2013)
The study was done to compare the effect of intra-peritoneal instillation of ropivacaine versus normal saline irrigation on post operative abdominal pain and shoulder pain in laparoscopic cholecystectomy. Ninety patients with symptomatic gall stones disease undergoing laparoscopic cholecystectomy were randomized in three groups. In study group A (n=30 patients) 0.5% of 30 ml (150 mg) of ropivacaine was instilled at gall bladder bed, and in study group B (n=30) 0.9% of 25 – 30 ml/kg of normal saline irrigation was done at gall bladder bed and sub-diaphragmatic space or control group C (n=30) none of above two intervention was done. Pain abdomen is worse during first 24 hours after laparoscopic cholecystectomy. At 6 hours pain abdomen was significantly less in group A compared to group B (p<.035). At 12 hours pain abdomen was less in group A and group B compared to control group. Intensity of shoulder tip pain was almost similar in group A and group B. Group A experienced significantly reduced shoulder tip pain at 6hours and 12 hours as compared to group C. Group B experienced less shoulder tip pain during first postoperative day as compared to control group. Intra-peritoneal instillation of ropivacaine is more effective than normal saline irrigation at early post-operative hours in reducing post-operative pain abdomen after laparoscopic cholecystectomy. However, intra-peritoneal instillation of ropivacaine and normal saline irrigation are comparable in its effect on shoulder tip pain.